Liz and the sand castle contest - Barkley, Callie (Barkley, Callie. Critter Club, 2015)
As her friends in the Critter Club animal shelter care for colorful aquarium fish, second-grader Liz and her family spend a long weekend at the beach, where Liz rescues a baby octopus and competes with an unfriendly young neighbor in a sand castle contest.